EFFECT OF LOCAL RIFAMYCIN APPLICATION ON EXPRESSION OF BMP-2 AND BONE REGENERATION - Emin Ün; İlker Özeç; Ufuk Taşdemir; Mustafa Kırtay; Hacı Hasan Esen; Mustafa Cihat Avunduk (Cumhuriyet University, 2017)
Objectives: The aim of this study was to evaluate effect of local rifamycin application on BMP-2 expression and bone healing.Materials and Methods: A standardized 5.0-mm- diameter critical size bone defect was created mandible angulus region. In the control group (8 rats) defects were left empty. In the Group 1 (n=8 rats) defect was irrigated with rifamycin solution and 25 mg rifamycin solution injected defect area at 1, 3, 7 days after surgery. In the group 2 (n=8 rats) defects were grafted with a gelatin sponge mixed 25 mg rifamycin solution. Rats were sacrificed at 21 days after surgery. Histological slides were prepared from defect site for both immunohistochemical analysis (bone morphogenetic protein-2 (BMP-2) antibody) and histomorphometric analysis. Data were analyzed using Mann Whitney U and Kruskall Wallis test.Results: The average new bone formation, number of osteoblast and new vessel formation count were increased more in both of experimental groups in comparison with control group. Anti-BMP-2 labelling (Cell count) was increased more in both of experimental groups in comparison with control group. Conclusion: Local rifamycin application has positive effects on BMP-2 expression and bone regeneration at critical sized bone defects.